161k views
5 votes
Match each function with its inverse function. use function composition to determine your answers.

Match each function with its inverse function. use function composition to determine-example-1

1 Answer

4 votes

QUESTION 1


\boxed {f(x) = 2x + 6 \to \: g(x) = (1)/(2)x - 3 }

The reason is that:


g(f(x)) = 2( (1)/(2) x - 3) + 6

Expand:


g(f(x)) = x - 6+ 6


g(f(x)) = x

QUESTION 2


\boxed {f(x) =3 - 2x \to \: g(x) = - (1)/(2)(x - 3)}

The reason that


g(f(x)) = - (1)/(2) (3 - 2x - 3)


g(f(x)) = - (1)/(2) (- 2x )


g(f(x)) =x

QUESTION 3


\boxed {f(x) = \sqrt[3]{3x}+ 2 \to \: g(x) = \frac{ {(x - 3)}^(3) }{3} }

The reason is that:


f(g(x)) = \sqrt[3]{ \frac{3 {(x - 2)}^(3) }{3} } + 2


f(g(x)) = x-2 + 2


f(g(x))=x

QUESTION 4


\boxed {f(x)=3\sqrt[3]{x + 2} \to \: g(x) = (1)/(27) {x}^(3) - 2}

The reason is that


f(g(x)) = 3 \sqrt[3]{ (1)/(27) {x}^(3) - 2 + 2}


f(g(x)) = 3 \sqrt[3]{ (1)/(27) {x}^(3) }


f(g(x)) = 3 * (1)/(3) x


f(g(x)) =x

User Damien Black
by
5.5k points